1997
DOI: 10.1021/jp9639657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adsorbed Iodine on the Dissolution and Deposition Reactions of Ag(100):  Studies by In Situ STM

Abstract: In situ scanning tunneling microscopy has been employed to determine the structure of iodine adlayers formed on Ag(100) and to evaluate the role of such adlayers in the dissolution and deposition reactions of the substrate in perchloric acid. In the double-layer potential region, iodine was found to possess a c(2 × 2) structure; this structure was unaffected by anodic dissolution of the Ag substrate. On both bare and I-pretreated Ag(100) surfaces, the anodic dissolution of Ag occurred exclusively at step-edges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 34 publications
7
48
1
Order By: Relevance
“…Calculations have shown that halide adlayers on (1 0 0) metal surfaces tend to form commensurate structures, mainly c(2 · 2), reflecting the higher substrate corrugation potential [14], even if it means overcoming the strong iodine-iodine repulsive interaction due to a smaller NNS below the van der Waals diameter (4.3 Å ). Well known examples are Pt [15], Pd [16], Ag [17].…”
Section: Further Discussionmentioning
confidence: 99%
“…Calculations have shown that halide adlayers on (1 0 0) metal surfaces tend to form commensurate structures, mainly c(2 · 2), reflecting the higher substrate corrugation potential [14], even if it means overcoming the strong iodine-iodine repulsive interaction due to a smaller NNS below the van der Waals diameter (4.3 Å ). Well known examples are Pt [15], Pd [16], Ag [17].…”
Section: Further Discussionmentioning
confidence: 99%
“…In this section, the discussion will be concentrated on the anisotropic layer-by-layer dissolution behavior of noble metal electrodes, palladium and gold, catalyzed by an adlayer of adsorbate on the substrate. Similar anisotropic anodic dissolution processes catalyzed by the ordered adsorbed layer have also been observed on S-Ni(100), [106] I-Ni (111), [107] IAg(100) [108] and Cl-Cu(hkl) [109][110][111][112] as well as Cl-Au(hkl) [29][30][31], which will be discussed in the next section in detail.…”
Section: Atomically Controlled Dissolution Of Noble Metalsmentioning
confidence: 55%
“…The presence of such a layer during dissolution is consistent with recent STM studies of other systems. [13][14][15][16][17][18][19][20][21] Acknowledgments Support for this work was provided by KDK Corporation and by St. Jude Medical. Aluminum foils were provided by KDK Corporation.…”
Section: Discussionmentioning
confidence: 99%
“…Itaya and co-workers found ordered adsorbed layers of I on Pd, Ag, and Ni, as well as S on Ni, during dissolution processes. [13][14][15][16] Interestingly, the presence of the I layer on Pd and the S layer on Ni suppressed oxide passivation of these surfaces. Suggs and Bard, Vogt et al, and Wan and Itaya all observed ordered chloride layers on Cu which remained on the surface during dissolution.…”
mentioning
confidence: 99%